Impact of Cyberprogram 2.0 on Different Types of School Violence and Aggressiveness - Garaigordobil, Maite; Martínez-Valderrey, Vanesa (Frontiers in Psychology, 2016)
Some antibullying interventions have shown positive outcomes with regard to reducing violence. The aim of the study was to experimentally assess the effects on school violence and aggressiveness of a program to prevent and reduce cyberbullying. The sample was comprised of a randomly selected sample of 176 adolescents (93 experimental, 83 control), aged 13-15 years. The study used a repeated measures pre-posttest design with a control group. Before and after the program, two assessment instruments were administered: the “Cuestionario de Violencia Escolar-Revisado” (CUVE-R [School Violence Questionnaire - Revised]; Álvarez-García et al., 2011) and the “Cuestionario de agresividad premeditada e impulsiva” (CAPI-A [Premeditated and Impulsive Aggressiveness Questionnaire]; Andreu, 2010). The intervention consisted of 19 one-hour sessions carried out during the school term. The program contains 25 activities with the following objectives: (1) to identify and conceptualize bullying/cyberbullying; (2) to analyze the consequences of bullying/cyberbullying, promoting participants’ capacity to report such actions when they are discovered; (3) to develop coping strategies to prevent and reduce bullying/cyberbullying; and (4) to achieve other transversal goals, such as developing positive variables (empathy, active listening, social skills, constructive conflict resolution, etc.). The pre-posttest ANCOVAs confirmed that the program stimulated a decrease in: (1) diverse types of school violence—teachers' violence towards students (ridiculing or publicly humiliating students in front of the class, etc.); students' physical violence (fights, blows, shoves... aimed at the victim, or at his or her property, etc.); students' verbal violence (using offensive language, cruel, embarrassing, or insulting words… towards classmates and teachers); social exclusion (rejection or exclusion of a person or group, etc.), and violence through Information and Communication Technologies (ICT) (violent behaviors by means of electronic instruments such as mobile phones and the Internet)—; and (2) premeditated and impulsive aggressiveness. Pre-posttest MANCOVA revealed differences between conditions with a medium effect size. This work contributes an efficacious intervention tool for the prevention and reduction of peer violence. The conclusions drawn from this study have interesting implications for educational and clinical intervention.